Correlation Study of Carbon Monoxide (CO) Air Exposure Level with Blood COHb Level of Basement Officer in Surabaya Mall - Safiatur Nur Rohmah (Universitas Airlangga, 2019)
Gas CO is formed as a result of incomplete combustion. The material containing carbon monoxide is gas emission from motorcycle vehicle which is toxic to humans. This study aims to analyze the correlation between CO gas that also known as Carbon monoxide gas in the air with COHb level of blood parking basement officers in Surabaya